Putative Repurposing of Lamivudine, a Nucleoside/Nucleotide Analogue and Antiretroviral to Improve the Outcome of Cancer and COVID-19 Patients - García-Trejo, José J.; Ortega, Raquel; Zarco-Zavala, Mariel (Frontiers in Oncology, 2021)
Lamivudine, also widely known as 3TC belongs to a family of nucleotide/nucleoside analogues of cytidine or cytosine that inhibits the Reverse Transcriptase (RT) of retroviruses such as HIV. Lamivudine is currently indicated in combination with other antiretroviral agents for the treatment of HIV-1 infection or for chronic Hepatitis B (HBV) virus infection associated with evidence of hepatitis B viral replication and active liver inflammation. HBV reactivation in patients with HBV infections who receive anticancer chemotherapy can be a life-threatening complication during and after the completion of chemotherapy. Lamivudine is used, as well as other antiretrovirals, to prevent the reactivation of the Hepatitis B virus during and after chemotherapy. In addition, Lamivudine has been shown to sensitize cancer cells to chemotherapy. Lamivudine and other similar analogs also have direct positive effects in the prevention of cancer in hepatitis B or HIV positive patients, independently of chemotherapy or radiotherapy. Recently, it has been proposed that Lamivudine might be also repurposed against SARS-CoV-2 in the context of the COVID-19 pandemic. In this review we first examine recent reports on the re-usage of Lamivudine or 3TC against the SARS-CoV-2, and we present docking evidence carried out in silico suggesting that Lamivudine may bind and possibly work as an inhibitor of the SARS-CoV-2 RdRp RNA polymerase. We also evaluate and propose assessment of repurposing Lamivudine as anti-SARS-CoV-2 and anti-COVID-19 antiviral. Secondly, we summarize the published literature on the use of Lamivudine or (3TC) before or during chemotherapy to prevent reactivation of HBV, and examine reports of enhanced effectiveness of radiotherapy in combination with Lamivudine treatment against the cancerous cells or tissues. We show that the anti-cancer properties of Lamivudine are well established, whereas its putative anti-COVID effect is under investigation. The side effects of lamivudine and the appearance of resistance to 3TC are also discussed.